A comparison of gender preference for tropical recreational rain forest in Malaysia - Hussein, Mohd Kher (Faculty of Design & Architecture, Universiti Putra Malaysia, 2018)
Malaysia’s recreational rainforests attract a significant number of visitors and they are an important tourism asset. Visitors are attracted by the scenic views of the forests as well as the biodiversity experiences of the forest ecosystems. These recreational forests are equipped with supporting facilities to attract visitors. This study investigates gender preferences of recreational rainforest landscape in Malaysia. The study objective is to compare gender preferences regarding recreational rainforest landscapes in relation to the efforts and commitments of managing the park by the responsible authority. Sg. Chongkak Recreational Forest in Selangor, Malaysia was selected as a case study. A photo-questionnaire survey was used to gather data from 119 expert participants. Results indicate that there is a statistically significant difference between male and female preferences for facilities (p=0.038) where a greater number of female (31.09%) rated the facilities in the study sites as good compared to their male counterparts (15.97%). Thus, gender preferences, in particularly women preferences, must be taken into account when developing landscape management plan for the park.